2009
DOI: 10.1152/ajpendo.00505.2009
|View full text |Cite
|
Sign up to set email alerts
|

Changed mitochondrial function by pre- and/or postpartum diet alterations in sheep

Abstract: In a sheep model, we investigated diet effects on skeletal muscle mitochondria to look for fetal programming. During pregnancy, ewes were fed normally (N) or were 50% food restricted (L) during the last trimester, and lambs born to these ewes received a normal (N) or a high-fat diet (H) for the first 6 mo of life. We examined mitochondrial function in permeabilized muscle fibers from the lambs at 6 mo of age (adolescence) and after 24 mo of age (adulthood). The postpartum H diet for the lambs induced an ϳ30% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
2
16
1
Order By: Relevance
“…In fact, only two significant results were found and both regarded THRA, which was downregulated in both BF muscle and subcutaneous adipose tissue. The different responses in muscles to pre-and postnatal dietary exposure could not be related to whether the muscles contained predominantly glycolytic (LD) or oxidative (cardiac and BF) muscle fibers (Jørgensen et al 2009). …”
Section: Effect Of Early Life Overnutrition In Growing Lambsmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, only two significant results were found and both regarded THRA, which was downregulated in both BF muscle and subcutaneous adipose tissue. The different responses in muscles to pre-and postnatal dietary exposure could not be related to whether the muscles contained predominantly glycolytic (LD) or oxidative (cardiac and BF) muscle fibers (Jørgensen et al 2009). …”
Section: Effect Of Early Life Overnutrition In Growing Lambsmentioning
confidence: 90%
“…After killing, thyroids and target organs were quickly excised and weighed and tissue samples were snap-frozen for later RNA extraction. Target tissues included liver (left lobe), two different skeletal muscles (the longissimus dorsi dominated by glycolytic type II fibers and biceps femoris dominated by oxidative type I fibers; Jørgensen et al (2009), cardiac muscle (central part of ventriculus sinister cordis), and two adipose tissues (visceral and subcutaneous sampled above the central part of longissimus dorsi).…”
Section: Experimental Animals and Experimental Designmentioning
confidence: 99%
“…The link between increased mitochondrial function and insulin resistance could be mediated via increased generation of reactive oxygen species (7), perhaps as a consequence of reduced state 4 respiration, as proposed in a recent study of sheep exposed to the combination of fetal under-and postnatal overnutrition (17).…”
Section: E47 Effects Of High-fat Overfeeding In Low-birth-weight Subjmentioning
confidence: 99%
“…In addition to total caloric intake [39,40], the magnitude of diet-induced thermogenesis has been determined to be dependent on the macronutrient composition of the diet [41] and previous obesity status [42]. Interestingly, it has been demonstrated that maternal energy restriction, as well as postnatal high-fat feeding, alters mitochondrial oxidative capacity and respiratory coupling ratio in sheep [43], suggesting that dietary composition may be able to directly alter muscle mitochondrial function.…”
Section: Measurements Of Skeletal Muscle Mitochondrial Uncoupling In mentioning
confidence: 99%